2020
DOI: 10.1038/s41598-020-64619-8
|View full text |Cite
|
Sign up to set email alerts
|

Neural network interpolation of exchange-correlation functional

Abstract: Density functional theory (DFT) is one of the most widely used tools to solve the many-body Schrodinger equation. The core uncertainty inside DFT theory is the exchange-correlation (XC) functional, the exact form of which is still unknown. Therefore, the essential part of DFT success is based on the progress in the development of XC approximations. Traditionally, they are built upon analytic solutions in low- and high-density limits and result from quantum Monte Carlo numerical calculations. However, there is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…The popularity of ML technique in the material science community is attributed to its computing speed and higher prediction accuracy as compared to conventional simulation methods. Recent studies have shown that ML methods can be used to design density functionals that can provide an alternate route for the DFT approach. By using the ML methods one can directly learn from the electron charge density and completely bypass solving the Kohn–Sham equations, thus enabling the evaluation of the total energy and other properties with far less computational cost than DFT.…”
mentioning
confidence: 99%
“…The popularity of ML technique in the material science community is attributed to its computing speed and higher prediction accuracy as compared to conventional simulation methods. Recent studies have shown that ML methods can be used to design density functionals that can provide an alternate route for the DFT approach. By using the ML methods one can directly learn from the electron charge density and completely bypass solving the Kohn–Sham equations, thus enabling the evaluation of the total energy and other properties with far less computational cost than DFT.…”
mentioning
confidence: 99%
“…One could use a neural network (NN) to learn the features from the raw density distribution in real space, but training features this way is data intensive, with 10 5 -10 6 training points used in recent works. 39,40 In addition, these NNs rely on a specific grid structure over which convolutions are performed, which could impede their use in realistic production calculations. Alternatively, one could project the density or density matrix onto atomic basis sets, as is done in NeuralXC and DeePKS, 13,14 but these two models do not incorporate any physical constraints into the features, making it infeasible to incorporate exact constraints into the model itself.…”
Section: The Cider Formalismmentioning
confidence: 99%
“…NN was first utilized as a functional form for XC potential by Tozer et al [20]. After that, several studies have been addressed the possibility of using NN to approximate XC functionals form [21][22][23][24][25][26]. Work by Nagai and co-authors [22] is especially worthy of note.…”
Section: Introductionmentioning
confidence: 99%